UHPC formwork-honeycomb steel reinforced concrete composite structure wall based on modular construction - GE SHANMING; LIU GEJIA; ZUO KAIYUAN; YANG YONG; ZHANG SHUCHEN; LI HUAYU (2024)
The invention discloses a UHPC (Ultra High Performance Concrete) formwork-honeycomb steel reinforced concrete composite structure wall based on modular construction, which is characterized by comprising a prefabricated UHPC formwork, and honeycomb H-shaped steel, a reinforcement cage and cast-in-place concrete which are positioned in the prefabricated UHPC formwork; honeycomb H-shaped steel is arranged in the height direction of the wall in a full-length mode, and reinforcement cages are arranged on the two sides of the honeycomb H-shaped steel in the horizontal direction. The prefabricated UHPC formwork shell is of a cavity structure with the upper portion and the lower portion open and the side direction closed and is formed by splicing a U-shaped UHPC formwork and a rectangular UHPC formwork or formed by splicing a U-shaped UHPC formwork, a rectangular UHPC formwork and an L-shaped UHPC formwork. The adjacent formworks are connected through the honeycomb H-shaped steel and the high-strength bolts. The wall